Naskah dan rekonstruksi sejarah lokal Islam; Contoh kasus dari Minangkabau - Fathurahman, Oman (UI Scholars Hub, 2005)
Manuscripts are not supposed to be something unknown to the public and possessed by limited circle of people. Manuscripts are cultural heritage of a nation the content of which reflects the ideas, knowledge, tradition, and the patterns of behavior of the past society. As such they can be of use to different segments of society. This paper discusses the benefits of manuscripts to the efforts of reconstructing Islamic intellectual history in Indonesia by studying the case of local manuscripts in the Minang region. These manuscripts are not only the products of a writing tradition that had developed strongly in the Minangkabau society, but also a reflection of the living tradition of the society.